Specific Volumetric Weight-Driven Shift in Microbiota Compositions With Saccharifying Activity Change in Starter for Chinese Baijiu Fermentation - Wang, Bowen; Wu, Qun; Xu, Yan; Sun, Baoguo (Frontiers in Microbiology, 2018)
Chinese starter Jiuqu, traditionally produced by spontaneous fermentation and always squeezed into bricks, serves as a vital saccharifying agent for simultaneous saccharification and fermentation of Chinese Baijiu. It is important to reveal the key saccharifying microbiota and the driving force to improve the quality of Jiuqu. Here we studied the compositions of the microbiota by high-throughput amplicons sequencing analysis in Jiuqu, and revealed eight bacterial and seven fungal genera as the dominant community members. Among them, Lactobacillus, Aspergillus, Pichia, Saccharomyces, Rhizopus were the main contributors of proteins by metaproteomics analysis. Whereas, only Lactobacillus, Pichia, Rhizopus appeared as key actors for saccharification by secreting three glycosidases and two glycosyltransferases, and it indicated they were the key saccharifying microbiota in Jiuqu. Especially, Rhizopus secreted the most abundant glucoamylase. Interestingly, these three active genera significantly decreased and the key saccharifying enzymes were down-expressed, when Jiuqu was produced in diffused shape with a low volumetric weight. Rhizopus microsporus, the main producer of glucoamylase, was positively correlated with volumetric weight of Jiuqu. It indicated volumetric weight was the major driving force of the key saccharifying microbiota in Jiuqu. This work provides deep insights of key saccharifying microbiota, and indicates the main driving force for the key microbe. Furthermore, this finding can contribute to the improvement of saccharifying agent for food fermentation.